Effects of Antiepileptics on Behavioral and Electroencephalographic Seizure Induced by Pentetrazol in Mice - Yusuke Watanabe; Kenshi Takechi; Akinori Fujiwara; Chiaki Kamei (Elsevier, 2010)
The present study was undertaken to investigate changes of the electroencephalogram (EEG) induced by pentetrazol (PTZ) in comparison with behavioral seizures in mice. Under pentobarbital anesthesia, mice were fixed to a stereotaxic apparatus, and electrodes were implanted into the frontal and occipital cortex. Behavioral and EEG changes were observed for 30 min following PTZ administration. After PTZ administration, mice showed myoclonic seizure (MCL) and clonic seizure (CL) in order. At the same time, spiking activity and spike-wave discharge in the cortex were observed. Phenobarbital, sodium valproate, diazepam, ethosuximide, and gabapentin caused a dose-dependent shortening of the duration of MCL and CL. In addition, they shortened the duration of spiking activity and spike-wave discharge dose-dependently. Moreover, phenytoin significantly inhibited the duration of spiking activity. It can be concluded that PTZ-induced spiking activity and spike-wave discharge serve as useful indices to assess the potential of antiepileptic activity in absence and MCLs in humans. Moreover, it is supposed that employing an index of EEG activity in addition to that of behavioral activity is desirable for objectivity. Keywords:: pentetrazol, myoclonic seizure, clonic seizure, electroencephalogram (EEG)